MENUMBUHKAN LITERASI DINI RAMAH ANAK DAN BERNUANSA KEARIFAN LOKAL BALI MELALUI LAGU ANAK DAN DONGENG - Ni Wayan Aryani (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
Children songs and fables are heritage of the Balinese ancestors to the next generation until now. Children songs and fables are transformed from oral form into written and animated video forms (second oral form) to create the assumption that their position, function, and meaning are very important for life, especially for early childhood. This paper focuses on the study of the meaning of local wisdom in children songs and fables that are sung and told to early childhood. This research is a descriptive qualitative research. Data collected by observation methods and note-taking technique. The data sources of this research are children songs and fables in collection of children’s stories books. The data sources consists of two children songs, namely Cakup-Cakup Balang and Peteng Bulan and one fable, namely Angsa teken Empas. The theory used in data analysis to express meaning is the semiotic structural theory. The results of data analysis found that children song titled Cakup-Cakup Balang and Peteng Bulan, and a fable entitled Angsa teken Empas have the meaning of Balinese local wisdom. Gaining of meaningful information of local wisdom in children songs (gending rare) and stories (satua) are traditions of growing early literacy that is child-friendly.